Contextualizing the challenges of education graduate students in the Philippines: translating needs analysis into strategic solutions - Nilo Jayoma Castulo; Arlyne C. Marasigan; Ma. Laarni D. Buenaventura; Jayson L. de Vera; Evelyn C. Bagaporo; Mark Ponce C. San Juan; Nathaniel S. Dalida (Discover Education)
Abstract The Philippine government has described the state of the education system, including graduate education, as both "miseducation" and a "failed system," resulting in poor quality. In response, the Philippine Commission on Higher Education has introduced a new policy implicitly called the "no publication, no graduation policy" and the implementation of transnational education law in the Philippines. This study explores the interest levels, research productivity, institutional support, and challenges faced by graduate students majoring in education, particularly in light of the recent implementation of the Commission on Higher Education Memo No. 15, Series of 2019. The study employed a descriptive quantitative online survey method with 198 education graduate students enrolled in the master's and doctoral degrees at Y University using Tinto's Theory of Student Departure. The findings showed that the majority of respondents show interest in research but lack confidence in their abilities, indicating a limited publication output. Regarding the top 12 challenges of graduate students at Y University were lack of time for research, lack of research capacity building, conflict of schedule between work and study, lack of mentoring support, extended cost for residency, heavy workload as a working student, lack of academic resources, financial problems, emotional concerns, unresponsive supervisor, lack of support from the library, and lack of motivation. Respondents predominantly prefer enhancing their research skills through structured training, seminars, and workshops. The study provides a range of recommendations to improve graduate education and the need for further research in this area.